Pengembangan Aplikasi PraMetaVirLab (Praktikum Metabolisme Virtual Laboratorium) Berbasis STEM Sebagai Media Pembelajaran Biologi KelasXII SMA/MA: (Development of the STEM-based PraMetaVirLab (Virtual Laboratory Metabolism Practicum) Application as a Media For Biology Learning) - Amalia Rahma, Rina; Wardhani , Irma Yuniar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
This research uses R&D (Research and Development) research with a 4D development model adapted to 3D (Define, Design, Develop). The objectives of this research are: 1) To determine the procedure for developing the STEM-based PraMetaVirLab (Virtual Laboratory Metabolism Practicum) application as a Biology Learning Media, 2) To determine the level of feasibility of the STEM-based PraMetaVirlab (Virtual Laboratory Metabolism Practicum) application as a Learning Media in Class XII SMA/ M.A. The test subjects in this research were students in class XII MIPA MA Raudlatus Shibyan. Data collection techniques through questionnaires, interviews and documentation. The sampling technique used is saturated sampling which is a type of non-probability sampling. The validation results from material experts obtained an assessment with an overall average percentage of 92.5% including the